2020
DOI: 10.1007/s10935-020-00584-2
|View full text |Cite
|
Sign up to set email alerts
|

Managing Implementation of a Parental Support Programme for Obesity Prevention in the School Context: The Importance of Creating Commitment in an Overburdened Work Situation, a Qualitative Study

Abstract: Health-related behaviours in children can be influenced by parental support programmes. The aim of this study was to explore barriers to and facilitators for the implementation of a parental support programme to promote physical activity and healthy dietary habits in a school context. We explored the views and experiences of 17 coordinating school nurses, non-coordinating school nurses, and school principals. We based the interview guide on the Consolidated Framework for Implementation Research. We held four f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The program is fully integrated into school routines and is moderately effective in improving dietary habits and physical activity in children and in one trial BMI in children with obesity was also reduced [ 34 ]. Process evaluations have consistently shown that the program is well received among teachers, parents, children and school nurses [ 16 , 38 40 , 52 ]. For these reasons, the HSS program is well-positioned for implementation research that aims to develop and test strategies that facilitate its uptake and use as part of routine practice in the school setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The program is fully integrated into school routines and is moderately effective in improving dietary habits and physical activity in children and in one trial BMI in children with obesity was also reduced [ 34 ]. Process evaluations have consistently shown that the program is well received among teachers, parents, children and school nurses [ 16 , 38 40 , 52 ]. For these reasons, the HSS program is well-positioned for implementation research that aims to develop and test strategies that facilitate its uptake and use as part of routine practice in the school setting.…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of context-specific implementation barriers and facilitators was based on previous process evaluations of the HSS program [ 16 , 38 , 39 , 41 ] and on two preparatory stakeholder workshops in each of the two municipalities participating in IMPROVE (Implementation strategy 1: Assess for readiness and identify barriers and facilitators). The CFIR framework was used as a guiding determinant framework due to its multilevel structure and its applicability to the municipality setting [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective school-based programs are characterized by active parental involvement, especially for younger children (3,4). Health promotion and prevention programs in schools involving parents can be challenging to implement since some school principals are uncertain about whether it is the role of the school to provide health guidance to parents (5) in addition to teaching children. Teachers describe barriers like the dense curriculum, lack of planning time, lack of support from principals and other personnel, and how projects come and go without feedback or sustainability (6), in addition to lack of parental engagement (5).…”
Section: Introductionmentioning
confidence: 99%